Role of Anterior Cingulate Cortex in Instrumental Learning: Blockade of Dopamine D1 Receptors Suppresses Overt but Not Covert Learning - Aly-Mahmoud, Mayada; Carlier, Pascal; Salam, Sherine A.; Houari Selmani, Mariam; Moftah, Marie Z.; Esclapez, Monique; Boussaoud, Driss (Frontiers in Behavioral Neuroscience, 2017)
Dopamine activity in anterior cingulate cortex (ACC) is essential for various aspects of instrumental behavior, including learning and effort based decision making. To dissociate learning from physical effort, we studied both observational (covert) learning and trial-and-error (overt) learning. If ACC dopamine activity is required for task acquisition, its blockade should impair both overt and covert learning. If dopamine is not required for task acquisition, but solely for regulating the willingness to expend effort for reward, blockade should impair overt learning but spare covert learning. Rats learned to push a lever for food rewards either with or without prior observation of an expert conspecific performing the same task. Before daily testing sessions, the rats received bilateral ACC microinfusions of SCH23390, a dopamine D1 receptor antagonist, or saline-control infusions. We found that dopamine blockade suppressed overt learning selectively, leaving task acquisition through observational (covert) learning intact. In subsequent testing sessions without dopamine blockade, rats recovered their overt-learning capacity but not their pre-treatment level of effort tolerance. These results suggest that ACC dopamine is not required for the acquisition of conditioned behaviors and that apparent learning impairments could instead reflect a reduced level of willingness to expend effort due to cortical dopamine blockade.